(untitled) (Research, Society and Development, 2021)
This article brings within two purposes. First it validated the scale of the New Ecological Paradigm (NEP) and then analyzed the ecocentrist and anthropocentric attitudes of university students from a Brazilian higher education institution. The original NPE scale of 15 items was used, in the form of a questionnaire and applied in a sample of 241 university students. Before the self-completion of the questionnaires, the university students did not receive the basic concepts of environmental attitudes. Confirmatory factor analysis techniques were used to test the structural model and statistical procedures to describe the sample as to its properties of similarities between the groups of students. The NEP was reduced to 13 items, proving to be reliable and valid to investigate structured and multidimensional environmental attitudes of university students. When analyzing the segmentation of university students, it was identified that women presented a more intense ecocentrist attitude than men. For the other segmentation groups in relation to age range, area of knowledge, semester in progress and course period, they did not present statistically significant differences. However, overall, the scores of university students indicated more ecocentrist than anthropocentrist attitudes. The convenience sample of part of the courses offered by the higher education institution may cause a bias in the research, considering as a limitation of this study. However, with the confirmation of the two-factor model, the results indicate consistency and guide future research to activities related to the environment, such as sustainable tourism, preservation against environmental impacts, among others.